2012
DOI: 10.1097/qai.0b013e31823edb6a
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Antiretroviral Treatment Programs in Rural Southern Africa

Abstract: Background Data on outcomes of antiretroviral treatment (ART) programs in rural sub-Saharan African are scarce. We describe early losses and long-term outcomes in six rural programs in Southern Africa with limited access to viral load monitoring and second-line ART. Methods Patients aged ≥16 years starting ART in two programs each in Zimbabwe, Mozambique and Lesotho were included. We evaluated risk factors for no follow-up after starting ART and mortality and loss to follow-up (LTFU) over 3 years of ART, usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
56
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 34 publications
11
56
1
Order By: Relevance
“…6 Furthermore, one year retention among treatment experienced CAG members at HC Nazareth was excellent (98.7%). Members reported multiple collateral benefits and commented that membership in CAG: 1) reduced time, effort, and money spent to get a monthly ART refill; 2) changed the perception by clinic staff as now they represent a group of patients; 3) induced peer support among fellow members, resulting in reports of improved adherence, home visits when a fellow member was sick, family and socio-economical support, empowerment to deal with stigma, 4) increased the openness with which people can adhere to their treatment; 5) generated interest and promoted health seeking behaviour of other community members, including community leaders; and 6) resulted in a feeling of relief and comfort.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…6 Furthermore, one year retention among treatment experienced CAG members at HC Nazareth was excellent (98.7%). Members reported multiple collateral benefits and commented that membership in CAG: 1) reduced time, effort, and money spent to get a monthly ART refill; 2) changed the perception by clinic staff as now they represent a group of patients; 3) induced peer support among fellow members, resulting in reports of improved adherence, home visits when a fellow member was sick, family and socio-economical support, empowerment to deal with stigma, 4) increased the openness with which people can adhere to their treatment; 5) generated interest and promoted health seeking behaviour of other community members, including community leaders; and 6) resulted in a feeling of relief and comfort.…”
Section: Discussionmentioning
confidence: 94%
“…2 Attrition is problematic; in rural Lesotho 55.4% were reported to be alive and on treatment at three years on ART, 13.5% had died, and 30.9% were lost to follow-up. 6 Scale-up of ART has been hampered by chronic understaffing and inadequate infrastructure in the healthcare system. 7 In 2009, drawing on a care model rolled out in Mozambique, 8,9 the Lesotho Ministry of Health decided to pilot Community ART Groups (CAG).…”
Section: Introductionmentioning
confidence: 99%
“…Stacked cumulative incidence curves were used to illustrate cumulative probability of death and LTFU over time for each annual cohort of adults starting ART [33].…”
Section: Methodsmentioning
confidence: 99%
“…2 Despite various interventions to improve patient adherence and retention in HIV care in Mozambique, the number of patients who discontinue treatment is still increasing. 1,3 For patients on ART, reduced loss to follow-up has important correlations with better clinical outcomes, including weight gain, recovery of CD4 count, reduction of viral load, and a lower likelihood of resistance, morbidity, and mortality. 25 In addition, studies have also shown that access to HIV care, initiation of ART and optimal adherence decreases the risk of sexually transmitting HIV.…”
Section: Introductionmentioning
confidence: 99%